Water-control sealing particles as well as preparation method and application thereof
By using water-controlled sealing particles prepared by using C9 petroleum resin and other materials in the carbonate reservoir of oil fields, the problem of sealing water layers under high temperature, high salt and acid conditions is solved, and oil-water selectivity and high sealing are achieved Intensity increases oil and gas production.
Patent Information
- Application Number
- CN202310711273.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-15
AI Technical Summary
The existing carbonate reservoir water control sealing technology in oilfields is difficult to effectively seal the water layer under high temperature, high salt and acidic conditions, resulting in poor oil and water selectivity and affecting oil and gas production.
Water-controlled sealing particles composed of C9 petroleum resin, rosin modified phenolic resin, terpene resin, epoxy resin, oil-soluble and water-soluble surfactants are prepared through specific kneading and granulation processes to form oil-water Selective and high strength bonding ability particles.
The water-controlled sealing particles exhibit good dispersion, solubility and sealing strength under high temperature, high salt and acidic conditions. They can selectively block the water layer without blocking the oil layer, significantly improving the oil and gas recovery rate .
Smart Images

Figure CN119144307A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil field water control and sealing, and in particular relates to a water control and sealing particle and a preparation method and application thereof. Background Art
[0002] Effectively utilizing reserves in oil-water complex areas is of great significance to increasing reserves and production. At present, the water avoidance height in oil-water complex areas is less than 30m. The existing top injection + parameter optimization composite fracture control water avoidance technology is suitable for more than 30m, and a new type of acid pressure water control sealing agent is required.
[0003] Water control and plugging technology for carbonate reservoirs in oil fields is divided into mechanical water plugging and chemical water plugging. Mechanical water plugging uses downhole tools such as packers and bridge plugs to plug high water-producing layers, exploit layers with lower water content, and improve crude oil recovery. Chemical water plugging is to inject chemical plugging agents into the formation for water plugging, which is divided into selective water plugging and non-selective water plugging. Non-selective water plugging technology is not selective for oil and water, and the oil layer and water layer are generally blocked. When the water layer is blocked, the oil layer is also blocked, affecting the increase in oil and gas production. Selective water plugging technology is to inject plugging agents that are selective for oil and water into the formation for water plugging. It forms plugging materials in the water layer, reduces the water phase permeability of the water-producing layer, reduces the water content of the oil well, and has a prominent oil-increasing effect.
[0004] Tuha and Huabei Oilfields in China have fracturing water control agents suitable for clastic reservoirs, which can achieve water control fracturing in wells with low water avoidance heights, but there is still a lack of acid pressure water control agents that are resistant to strong acids and temperatures of 120°C to 140°C. In addition, existing plugging agents are mainly used for water plugging under high mineralization and high temperature conditions, and are difficult to adapt to the presence of acidic substances in the formation. Therefore, there is still a lot of room for improvement in the technology and performance of existing plugging agents. The research and development of acid pressure water control sealing agents will have an important impact on the development of existing oil reservoirs and the economic benefits that will ultimately be shown. Summary of the invention
[0005] One of the present inventions provides a water-controlling and sealing particle, the raw materials of which include C9 petroleum resin, rosin-modified phenolic resin, terpene resin, epoxy resin, oil-soluble surfactant and water-soluble surfactant.
[0006] According to a specific embodiment of the present invention, the mass of the water-controlling and sealing particles is taken as 100%, the amount of the C9 petroleum resin is 41.5wt% to 50wt%, the amount of the rosin-modified phenolic resin is 15wt% to 16.5wt%, the amount of the terpene resin is 22wt% to 30wt%, the amount of the epoxy resin is 1.7wt% to 4wt%, the amount of the oil-soluble surfactant is 7wt% to 8wt%, and the amount of the water-soluble surfactant is 2.5wt% to 3wt%;
[0007] Preferably, taking the mass of the water-controlling and sealing particles as 100%, the amount of the C9 petroleum resin is 41.9wt% to 49.8wt%, the amount of the rosin-modified phenolic resin is 15wt% to 16.5wt%, the amount of the terpene resin is 22.5wt% to 29.7wt%, the amount of the epoxy resin is 1.7wt% to 3.8wt%, the amount of the oil-soluble surfactant is 7.3wt% to 7.7wt%, and the amount of the water-soluble surfactant is 2.5wt% to 2.7wt%.
[0008] According to a specific embodiment of the present invention, the C9 petroleum resin has a weight average molecular weight of 2500 to 3000, a density of 1.08 g / mL to 1.14 g / mL, and a softening point of 130° C. to 150° C.; and / or
[0009] The rosin-modified phenolic resin has a weight average molecular weight of 150,000 to 166,000, a density of 1.1 g / mL to 1.2 g / mL, and a softening point of 170° C. to 180° C.; and / or
[0010] The terpene resin has a weight average molecular weight of 650 to 1250, a density of 0.96 g / mL to 0.98 g / mL, and a softening point of 140° C. to 160° C.; and / or
[0011] The epoxy resin has a weight average molecular weight of 365 and a density of 1.15 g / mL to 1.2 g / mL.
[0012] According to a specific embodiment of the present invention, the oil-soluble surfactant is glyceryl monostearate; and / or
[0013] The water-soluble surfactant is polyethylene glycol monostearate.
[0014] According to a specific embodiment of the present invention, the particle size of the water-controlling and sealing particles is 10 mesh to 20 mesh and / or 100 mesh to 200 mesh.
[0015] The second aspect of the present invention provides a method for preparing the water-controlling and sealing particles according to the first aspect of the present invention, which comprises the following steps:
[0016] 1) performing a first mixing of the rosin-modified phenolic resin and the terpene resin to obtain a first mixture;
[0017] 2) performing a second mixing of the first mixture, C9 petroleum resin and epoxy resin to obtain a second mixture;
[0018] 3) mixing the second mixture with an oil-soluble surfactant and a water-soluble surfactant to undergo gelation transformation to obtain a third mixture;
[0019] 4) Granulating the third mixture to obtain the water-controlling and sealing granules.
[0020] According to a specific embodiment of the present invention, the step 3) is carried out under stirring;
[0021] Preferably, the stirring speed in the first kneading process, the stirring speed in the second kneading process and the stirring speed in step 3) are independently 3000 r / min to 4000 r / min.
[0022] According to a specific embodiment of the present invention, when the viscosity of the second kneaded product reaches 800 mPa.s, stirring is stopped to obtain the second mixture; and / or
[0023] In step 3), when the viscosity of the product obtained by the gel transformation reaches 1000 mPa.s, stirring is stopped and the mixture is cooled to obtain the third mixture;
[0024] Preferably, the cooling is cooling to room temperature.
[0025] According to a specific embodiment of the present invention, the temperatures of the first mixing and the second mixing are independently 160° C. to 163° C.; and / or
[0026] In step 3), the gelation transition is performed at 170°C.
[0027] According to a specific embodiment of the present invention, the first kneading and the second kneading are performed using a kneader.
[0028] Use of the water-controlling and sealing particles according to one of the present inventions or the water-controlling and sealing particles prepared by the method according to the second present invention as water-controlling and sealing agents for acid fracturing in water plugging of high-temperature and high-salinity fracture-cavity carbonate reservoirs;
[0029] Preferably, the HCl content in the acid fracturing fluid is up to 5 wt%; and / or the high temperature is up to 140° C.; and / or the high salt has a mineralization degree of up to 210,000 mg / L.
[0030] Beneficial effects of the present invention:
[0031] In view of the problem that the water-controlling sealing agent in the prior art is not resistant to strong acid and temperature of 120 to 140° C., the present invention provides a water-controlling sealing particle and a preparation method and application thereof.
[0032] 1) The density of the water-controlling and sealing particles provided by the present invention is between 1.1 and 1.2 g / ml, and they have good dispersibility in the carrier liquid and a wide range of applications;
[0033] 2) The water-controlling and sealing particles provided by the present invention have a solubility rate of more than 90% in kerosene at a temperature range of room temperature to 140°C, and are insoluble in water with a salinity of 210,000. They have oil-water selectivity, block water without blocking oil, and can selectively block water;
[0034] 3) The softening point of the water-controlling and sealing particles provided by the present invention is between 110 and 140°C; at 110 to 140°C, the complete bonding time of the water-controlling and sealing particles in a high-acid and high-salt solution of 210,000 mineralization degrees containing 5wt% HCl is 3 to 4.6 hours, and the water-controlling and sealing particles have good resistance to high temperature, high salt and acid;
[0035] 4) Under the conditions of 110 to 140°C and 210,000 mineralization degrees, the water control and sealing particles provided by the present invention can achieve high-strength bonding; after the water control and sealing particles are fully bonded, they have good resistance to high temperature, high salt and acid: under the conditions of high temperature, high acid and high salt of 5wt% HCl aqueous solution at 110 to 140°C and 210,000 mineralization degrees, the sealing pressure bearing strength for cracks with a width of 1 to 2 mm is about 10 to 15 MPa, with high sealing strength and good sealing effect;
[0036] In summary, the water-controlling sealing particles provided by the present invention have good dispersibility in the carrying liquid, oil-water selectivity, high strength after complete bonding, high temperature resistance, high salt resistance and good acid resistance, and have strong plugging ability under high temperature, high acid and high salt conditions, and can be used as water-controlling sealing agents after acid pressing. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The figure shows the changes of the water injection pressure before plugging, the injection pressure during the injection of water-controlling and sealing particles, and the water injection pressure after plugging as a function of the injection volume during the water-controlling and sealing simulation experiment of the water-controlling and sealing particles prepared in Example 1 on a 1 mm wide crack at 110°C;
[0038] Figure 2 The figure shows the changes of the water injection pressure before plugging, the injection pressure during the injection of water-controlling and sealing particles, and the water injection pressure after plugging as a function of the injection volume during the water-controlling and sealing simulation experiment of the water-controlling and sealing particles prepared in Example 2 on a 1 mm wide crack at 110°C;
[0039] Figure 3 The figure shows the changes of the water injection pressure before plugging, the injection pressure during the injection of water-controlling and sealing particles, and the water injection pressure after plugging as a function of the injection volume during the water-controlling and sealing simulation experiment of the water-controlling and sealing particles prepared in Example 3 on a 2 mm wide crack at 140°C;
[0040] Figure 4The diagram shows the changes in the water injection pressure before plugging, the injection pressure during the injection of water-controlling sealing particles, and the water injection pressure after plugging during the water-controlling sealing simulation experiment of a 2 mm wide crack at 140°C prepared in Example 4 as a function of the injection volume. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation manner does not constitute a limitation of the present invention under any circumstances.
[0042] The kneading machine used in Examples 1 to 4 was purchased from Laizhou Runkai Trading Co., Ltd., model NHL--100.
[0043] The raw materials used in Examples 1 to 4 are:
[0044] C9 petroleum resin: purchased from Shenzhen Jitian Chemical Co., Ltd., with a weight average molecular weight of 2500 to 3000, a density of 1.08 to 1.14 g / mL, and a softening point of 130 to 150°C;
[0045] Rosin modified phenolic resin: purchased from Shenzhen Jitian Chemical Co., Ltd., with a weight average molecular weight of 150087 to 166460, a density of 1.10 to 1.20 g / mL, and a softening point of 170 to 180°C;
[0046] Terpene resin: purchased from Shenzhen Yoshida Chemical Co., Ltd., with a weight average molecular weight of 650 to 1250, a density of 0.96 to 0.98 g / mL, and a softening point of 140 to 160°C;
[0047] Epoxy resin: purchased from Shenzhen Jitian Chemical Co., Ltd., with a weight average molecular weight of 365 and a density of 1.15 to 1.20 g / mL;
[0048] Glyceryl monostearate and polyethylene glycol monostearate were purchased from Beijing Inokai Co., Ltd.
[0049] The following room temperatures are all 25°C.
[0050] Example 1
[0051] 1) Weigh 15.23 g of rosin-modified phenolic resin and 22.71 g of terpene resin and add them into a kneader for first mixing: adjust the temperature of the kneader to 160° C., adjust the speed to 3000 r / min, and stir until the mixture is uniformly mixed to obtain a first mixture;
[0052] 2) Add 49.53 g of C9 petroleum resin and 3.79 g of epoxy resin into the kneader for second mixing: adjust the speed to 4000 r / min and mix and stir until the viscosity reaches 800 mPa·s, then stop stirring to form a second mixture;
[0053] 3) adding the second mixture obtained in step 2), 7.33 g of the oil-soluble surfactant glyceryl monostearate and 2.55 g of the water-soluble surfactant polyethylene glycol monostearate to a reactor, maintaining a stirring speed of 4000 r / min and continuously stirring and heating to 170° C. for gelation transformation, observing at intervals until the system in the reactor is gelled and the viscosity reaches 1000 mPa·s, stopping stirring, cooling to room temperature, and standing to obtain a third mixture;
[0054] 4) The third mixture obtained in step 3) is crushed, sieved and granulated to obtain light yellow solid particles of 10 to 20 mesh and 100 to 200 mesh, which are the water-controlling and sealing particles of the present invention.
[0055] Example 2
[0056] 1) Weigh 15.65 g of rosin-modified phenolic resin and 22.71 g of terpene resin and add them into a kneader for first mixing: adjust the temperature of the kneader to 160° C., adjust the speed to 3000 r / min, and stir until the mixture is uniformly mixed to obtain a first mixture;
[0057] 2) Continue to add 49.53 g of C9 petroleum resin and 1.73 g of epoxy resin into the kneader for second mixing: adjust the speed to 4000 r / min and mix and stir until the viscosity reaches 800 mPa·s, then stop stirring to form a second mixture;
[0058] 3) adding the second mixture obtained in step 2), 7.33 g of the oil-soluble surfactant glyceryl monostearate and 2.55 g of the water-soluble surfactant polyethylene glycol monostearate to a reactor, maintaining a stirring speed of 4000 r / min and continuously stirring and heating to 170° C. for gelation transformation, observing at intervals until the system in the reactor is gelled and the viscosity reaches 1000 mPa·s, stopping stirring, cooling to room temperature, and standing to obtain a third mixture;
[0059] 4) The third mixture obtained in step 3) is crushed, sieved and granulated to obtain light yellow solid particles of 10 to 20 mesh and 100 to 200 mesh, which are the water-controlling and sealing particles of the present invention.
[0060] Example 3
[0061] 1) Weigh 15.65 g of rosin-modified phenolic resin and 25.36 g of terpene resin and add them into a kneader for first mixing: adjust the temperature of the kneader to 160° C., adjust the speed to 3000 r / min, and stir until the mixture is uniformly mixed to obtain a first mixture;
[0062] 2) Continue to add 42.31 g of C9 petroleum resin and 1.73 g of epoxy resin into the kneader for second mixing: adjust the speed to 4000 r / min and mix and stir until the viscosity reaches 800 mPa·s, then stop stirring to form a second mixture;
[0063] 3) adding the second mixture obtained in step 2), 7.33 g of the oil-soluble surfactant glyceryl monostearate and 2.55 g of the water-soluble surfactant polyethylene glycol monostearate to a reactor, maintaining a stirring speed of 4000 r / min and continuously stirring and heating to 170° C. for gelation transformation, observing at intervals until the system in the reactor is gelled and the viscosity reaches 1000 mPa·s, stopping stirring, cooling to room temperature, and standing to obtain a third mixture;
[0064] 4) The third mixture obtained in step 3) is crushed, sieved and granulated to obtain light yellow solid particles of 10 to 20 mesh and 100 to 200 mesh, which are the water-controlling and sealing particles of the present invention.
[0065] Example 4
[0066] 1) Weigh 15.65 g of rosin-modified phenolic resin and 28.43 g of terpene resin and add them into a kneader for first mixing: adjust the temperature of the kneader to 160° C., adjust the speed to 3000 r / min, and stir until the mixture is uniformly mixed to obtain a first mixture;
[0067] 2) Add 40.10 g of C9 petroleum resin and 1.73 g of epoxy resin into the kneader for second mixing: adjust the speed to 4000 r / min and mix and stir until the viscosity reaches 800 mPa·s, then stop stirring to form a second mixture;
[0068] 3) adding the second mixture obtained in step 2), 7.33 g of the oil-soluble surfactant glyceryl monostearate and 2.55 g of the water-soluble surfactant polyethylene glycol monostearate to a reactor, maintaining a stirring speed of 4000 r / min and continuously stirring and heating to 170° C. for gelation transformation, observing at intervals until the system in the reactor is gelled and the viscosity reaches 1000 mPa·s, stopping stirring, cooling to room temperature, and standing to obtain a third mixture;
[0069] 4) The third mixture obtained in step 3) is crushed, sieved and granulated to obtain light yellow solid particles of 10 to 20 mesh and 100 to 200 mesh, which are the water-controlling and sealing particles of the present invention.
[0070] Performance evaluation of water-controlling and sealing particles
[0071] Test Example 1
[0072] ⅰ Determination of the density of water-controlled sealing particles
[0073] At room temperature, the density of the water-controlling and sealing particles prepared in Examples 1 to 4 was measured by the water displacement method. The specific results are shown in Table 1.
[0074] Table 1. Density of water-controlled sealing particles (25°C)
[0075] Serial number <![CDATA[Density / (g / cm 3 )]]> Example 1 1.13 Example 2 1.16 Example 3 1.16 Example 4 1.19
[0076] The data in Table 1 show that the density of the water-controlling and sealing particles prepared in Examples 1 to 4 is 1.13 to 1.19 g / cm 3 , which is conducive to its uniform dispersion in the carrying liquid.
[0077] ⅱ Determination of softening point of water-controlled sealed particles
[0078] The softening points of the water-controlling and sealing particles prepared in Examples 1 to 4 were measured using a Vicat softening point tester. The specific results are shown in Table 2.
[0079] ⅲ Determination of the complete adhesion time of water-controlled sealing particles under high temperature, high salt and high acid conditions
[0080] a. Prepare a high-acid, high-salt solution: weigh 32.19gCaCl2, 10.39gMgCl2·6H2O, 0.3909gNa2SO4, 0.2001gNaHCO3, 0.0097gKI, 0.3740gKBr, 0.0958gKCl, and 176.71gNaCl in a beaker containing 1L of water and stir until the solution is clear and transparent without residue, which is 210,000 mineralization degree water; weigh 86.5g of the prepared 210,000 mineralization degree water in a beaker, add 13.5g of 37% HCl solution by mass, stir and mix evenly, and obtain a 5wt% HCl solution with a mineralization degree of 210,000, which is a high-acid, high-salt solution;
[0081] b. Weigh 4 portions of the high-acid and high-salt solution prepared in step a, 500 mL each, and add them to 4 high-temperature and high-pressure crystallization reactors, and then weigh 5 g of each of the water-controlling and sealing particles prepared in Examples 1 to 4, and add them to the high-temperature and high-pressure crystallization reactors containing the high-acid and high-salt solution;
[0082] c. The temperature of the four high-temperature and high-pressure crystallization reactors containing the water-controlling sealing particles and the high-acid and high-salt solution in step b was adjusted to 110° C., so that the water-controlling sealing particles were bonded. The bonding of the water-controlling sealing particles was observed during the experiment, and the time to achieve complete bonding (referring to the time when the bonded water-controlling sealing particles completely lost fluidity) was recorded;
[0083] According to the above method, the temperature of the high temperature and high pressure crystallization reactor in step c was adjusted to 120°C, 130°C, and 140°C, and the time for the water-controlled sealing particles prepared in Examples 1 to 4 to reach complete bonding at different temperatures was measured. The specific results are shown in Table 2.
[0084] Table 2. Softening point of water-controlled sealing particles and time to achieve complete bonding at different temperatures
[0085]
[0086] The data in Table 2 show that the softening point of the water-controlling and sealing particles prepared in Examples 1 to 4 is relatively high, specifically 109 to 138°C, and complete bonding is achieved within 3 to 4.6 hours at 110 to 140°C, proving that the water-controlling and sealing particles have good high temperature resistance, high salt resistance and acid resistance.
[0087] ⅳ Determination of oil solubility of water-controlled sealing particles
[0088] 1) Prepare high mineralization water: weigh 32.19g CaCl2, 10.39g MgCl2·6H2O, 0.3909g Na2SO4, 0.2001g NaHCO3, 0.0097g KI, 0.3740g KBr, 0.0958g KCl, 176.71g NaCl in a beaker containing 1L water and stir until the solution is clear and transparent without residue, which is 210,000 mineralization water;
[0089] 2) Experimental oil: kerosene
[0090] 3) Weigh two portions of the water-controlling and sealing particles prepared in any one of Examples 1 to 4, each portion weighing 5 g, and add them to two beakers containing 500 mL of 210,000-degree mineralization water and 500 mL of kerosene, respectively, and let stand at the experimental temperature. Every 10 minutes, filter, dry and weigh the water-controlling and sealing particles in the beaker until the mass of the filtered water-controlling and sealing particles after drying remains unchanged, and calculate the dissolution rate;
[0091] According to the above method, at room temperature, 110°C, 120°C, 130°C, and 140°C, the solubility rates of the water-controlling and sealing particles prepared in Examples 1 to 4 in 210,000 mineralization degree water and kerosene were respectively measured. The specific results are shown in Tables 3 to 7.
[0092] Table 3. Dissolution rate of water-controlled sealing particles in 210,000 salinity water and kerosene at 25°C
[0093] Serial number Dissolution rate in 210,000 mineralization water (25℃) / % Solubility in kerosene (25℃) / % Example 1 Insoluble 98.6 Example 2 Insoluble 95.5 Example 3 Insoluble 90.4 Example 4 Insoluble 90.4
[0094] Table 4. Dissolution rate of water-controlled sealing particles in 210,000 salinity water and kerosene at 110°C
[0095] Serial number Dissolution rate in 210,000 mineralization water (110℃) / % Solubility in kerosene (110℃) / % Example 1 Insoluble 98.9 Example 2 Insoluble 96.6 Example 3 Insoluble 95.5 Example 4 Insoluble 95.5
[0096] Table 5. Dissolution rate of water-controlled sealing particles in 210,000 salinity water and kerosene at 120°C
[0097]
[0098]
[0099] Table 6. Dissolution rate of water-controlled sealing particles in 210,000 salinity water and kerosene at 130°C
[0100] Serial number Dissolution rate in 210,000 mineralization degrees water (130℃) / % Solubility in kerosene (130℃) / % Example 1 Insoluble 99.1 Example 2 Insoluble 97.4 Example 3 Insoluble 97.0 Example 4 Insoluble 97.0
[0101] Table 7. Dissolution rate of water-controlled sealing particles in 210,000 salinity water and kerosene at 140°C
[0102] Serial number Dissolution rate in 210,000 mineralization water (140℃) / % Solubility in kerosene (140℃) / % Example 1 Insoluble 99.3 Example 2 Insoluble 97.5 Example 3 Insoluble 97.2 Example 4 Insoluble 97.2
[0103] It can be seen from Tables 3 to 7 that the water-controlling and sealing particles prepared in Examples 1 to 4 are insoluble in 210,000 mineralization degree water at 25 to 140°C, but have good solubility in kerosene, and the solubility rates at 25 to 140°C are all above 90%. Specifically: at 25°C, the solubility rate of the water-controlling and sealing particles prepared in Examples 1 to 4 in kerosene is 90.4% to 98.6%; at 110°C, the solubility rate of the water-controlling and sealing particles prepared in Examples 1 to 4 in kerosene is 95.5% to 98.9%; at 120°C, the solubility rate of the water-controlling and sealing particles prepared in Examples 1 to 4 in kerosene is 96.6% to 99%; at 130°C, the solubility rate of the water-controlling and sealing particles prepared in Examples 1 to 4 in kerosene is 97% to 99.1%; at 140°C, the solubility rate of the water-controlling and sealing particles prepared in Examples 1 to 4 in kerosene is 97.2% to 99.3%. It can be seen that the water-controlling and sealing particles provided by the present invention have oil-water selectivity, can block water without blocking oil, and can selectively block water.
[0104] Test Example 2
[0105] The water control and sealing particles prepared in Examples 1 to 4 were used to carry out a water control and sealing simulation experiment under high temperature, high acid and high salt conditions to evaluate the sealing performance of the water control and sealing particles under high temperature, high acid and high salt conditions.
[0106] The specific steps are as follows:
[0107] ① Weigh the water-controlling and sealing particles prepared in any one of Examples 1 to 4 in a mass ratio of 2:1, i.e., 10 to 20 mesh water-controlling and sealing particles and 100 to 200 mesh water-controlling and sealing particles, and mix them evenly to obtain the composite water-controlling and sealing particles for use;
[0108] ② Load the core into a steel plate of appropriate width to simulate the crack width required for the experiment, and install the core in the diversion chamber;
[0109] ③ Install the diversion chamber in the intermediate container and apply a confining pressure of 20MPa;
[0110] ④ Turn on the ISCO pump and select the constant flow mode. First, carry out the first water drive process (i.e., water drive before plugging), and stop the injection process after the injection pressure stabilizes. Then inject 50FV (i.e., 50 times the gap volume) of an aqueous solution containing 0.5wt% hydroxypropyl guar gum and 0.2wt% borax with a mineralization of 210,000, which carries the compounded water control and sealing particles obtained in step ①, so that the injection amount of the compounded water control and sealing particles reaches 0.5FV (i.e., 0.5 times the gap volume). After the injection is completed, heat the diversion chamber to the experimental temperature and maintain it for 5 hours to allow the water control and sealing particles to completely adhere, and then carry out the second water drive process (i.e., water drive after plugging), specifically using a 5wt% HCl aqueous solution with a mineralization of 210,000 for displacement. The computer records the pressure value and liquid output of the whole process;
[0111] ⑤ When the plugging body formed by the complete adhesion of the water-controlling sealing particles is broken and the injected water flows out from the outlet, stop the experiment and record the maximum pressure of the process, which is the sealing pressure strength of the water-controlling sealing particles for the crack of the same width at the experimental temperature. Finally, unload the confining pressure and pump pressure, take out the core, and record the data.
[0112] According to the above method, the water-controlling sealing particles prepared in Example 1 were used to test a 1 mm wide crack at an experimental temperature of 110°C; the water-controlling sealing particles prepared in Example 2 were used to test a 1 mm wide crack at experimental temperatures of 110°C and 120°C; the water-controlling sealing particles prepared in Example 3 were used to test a 2 mm wide crack at experimental temperatures of 110°C, 120°C, 130°C and 140°C; the water-controlling sealing particles prepared in Example 4 were used to test a 2 mm wide crack at experimental temperatures of 110°C, 120°C, 130°C and 140°C. The experimental results are shown in FIG. Figures 1 to 4 and Table 8.
[0113] Table 8. Sealing pressure strength after water-control sealing particles are fully bonded
[0114]
[0115] The following table 8 and Figures 1 to 4 Analysis of the results of the water control and plugging simulation experiment:
[0116] Table 8 shows the sealing pressure bearing capacity of the water-controlling sealing particles prepared in Examples 1 to 4 for sealing cracks of different widths at different temperatures: at 110°C, the sealing pressure bearing strengths of the water-controlling sealing particles prepared in Examples 1 and 2 for 1 mm wide cracks are 10.65 MPa and 11.64 MPa, respectively; at 120°C, the sealing pressure bearing strength of the water-controlling sealing particles prepared in Example 2 for 1 mm wide cracks is 10.25 MPa; at 120°C, the sealing pressure bearing strength of the water-controlling sealing particles prepared in Example 3 for 1 mm wide cracks is 10.65 MPa and 11.64 MPa, respectively. The sealing compressive strength for 2 mm wide cracks at 110°C, 120°C, 130°C and 140°C are 11.78 MPa, 11.20 MPa, 10.65 MPa and 10.06 MPa respectively; the sealing compressive strength for 2 mm wide cracks at 110°C, 120°C, 130°C and 140°C prepared in Example 4 are 15.21 MPa, 14.11 MPa, 12.35 MPa and 10.34 MPa respectively. Figures 1 to 4 The following table shows the changes of injection pressure before plugging, injection pressure during injection of water-controlling and sealing particles, and injection pressure after plugging as a function of injection volume during the water-controlling and sealing simulation experiment of 1 mm wide cracks or 2 mm wide cracks at different temperatures prepared by water-controlling and sealing particles in Examples 1 to 4. Figures 1 to 4 It can be seen that in the pre-plugging water drive stage, due to the existence of large cracks, the injection pressure of water drive is very small and remains stable at 0.01MPa for a long time. Then, with the injection of water control and sealing particles, the injection pressure shows a continuous upward trend. After injecting 0.5FV water control and sealing particles, Figures 1 to 4 The injection pressures in the wells reached 9.62MPa (1mm wide crack), 8.01MPa (1mm wide crack), 8.32MPa (2mm wide crack) and 7.85MPa (2mm wide crack) respectively, achieving good injection. The injection of water-controlling sealing particles was stopped, and the temperature was raised until the water-controlling sealing particles were bonded, and then the plugging water drive was carried out. At this time, due to the bonding of the water-controlling sealing particles to form a plugging body, the injection pressure of the plugging water drive increased sharply until it broke through the plugging body. Figures 1 to 4The pressures when the sealing body breaks through are 10.65MPa (110℃, 1mm wide crack), 11.64MPa (110℃, 1mm wide crack), 10.06MPa (140℃, 2mm wide crack) and 10.34MPa (140℃, 2mm wide crack), which are the sealing pressure strength of the water-controlling sealing particles. Combined with the steps of the water control and plugging simulation experiment, it can be known that the carrying liquid carrying the water control and sealing particles is a high-salt solution, that is, an aqueous solution containing 0.5wt% hydroxypropyl guar gum and 0.2wt% borax with a mineralization of 210,000, and a high-acid and high-salt solution is used for the second water drive, that is, a 5wt% HCl aqueous solution with a mineralization of 210,000, which shows that the water control and sealing particles provided by the present invention can achieve high-strength bonding under high temperature and high salt conditions; after the water control and sealing particles are completely bonded, the sealing pressure bearing strength for cracks with a width of 1mm and 2mm in a high temperature, high acid and high salt environment is above 10MPa, the sealing strength is relatively high, and the sealing effect is relatively good, which further shows that the water control and sealing particles are resistant to high temperature, high salt and acid after being completely bonded, and can be used as water control sealing agents in water control and sealing operations after acid fracturing.
[0117] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A water-controlling and sealing particle, the raw materials of which include C 9 Petroleum resin, rosin-modified phenolic resin, terpene resin, epoxy resin, oil-soluble surfactant and water-soluble surfactant.
2. The water-controlling and sealing particles according to claim 1, It is characterized in that The mass of the water-controlling and sealing particles is taken as 100%, and the C 9 The amount of petroleum resin used is 41.5wt% to 50wt%, the amount of rosin-modified phenolic resin used is 15wt% to 16.5wt%, the amount of terpene resin used is 22wt% to 30wt%, the amount of epoxy resin used is 1.7wt% to 4wt%, the amount of oil-soluble surfactant used is 7wt% to 8wt%, and the amount of water-soluble surfactant used is 2.5wt% to 3wt%.
3. The water-controlling and sealing particles according to claim 1 or 2, It is characterized in that The C 9 The petroleum resin has a weight average molecular weight of 2500 to 3000, a density of 1.08 g / mL to 1.14 g / mL, and a softening point of 130° C. to 150° C.; and / or The rosin-modified phenolic resin has a weight average molecular weight of 150,000 to 166,000, a density of 1.1 g / mL to 1.2 g / mL, and a softening point of 170° C. to 180° C.; and / or The terpene resin has a weight average molecular weight of 650 to 1250, a density of 0.96 g / m3 to 0.98 g / mL, and a softening point of 140° C. to 160° C.; and / or The epoxy resin has a weight average molecular weight of 365 and a density of 1.15 g / mL to 1.2 g / mL.
4. The water-controlling and sealing particles according to any one of claims 1 to 3, It is characterized in that The oil-soluble surfactant is glyceryl monostearate; and / or The water-soluble surfactant is polyethylene glycol monostearate.
5. The water-controlling and sealing particles according to any one of claims 1 to 4, It is characterized in that The particle size of the water-controlling and sealing particles is 10 mesh to 20 mesh and / or 100 mesh to 200 mesh.
6. A method for preparing the water-controlling and sealing particles according to any one of claims 1 to 5, comprising the following steps: 1) performing a first mixing of the rosin-modified phenolic resin and the terpene resin to obtain a first mixture; 2) making the first mixture and C 9 The petroleum resin and the epoxy resin are mixed for the second time to obtain a second mixture; 3) mixing the second mixture with an oil-soluble surfactant and a water-soluble surfactant to undergo gelation transformation to obtain a third mixture; 4) Granulating the third mixture to obtain the water-controlling and sealing granules.
7. The method according to claim 6, It is characterized in that The step 3) is carried out under stirring; Preferably, the stirring speed in the first kneading process, the stirring speed in the second kneading process and the stirring speed in step 3) are independently 3000 r / min to 4000 r / min.
8. The method according to claim 7, It is characterized in that When the viscosity of the second kneaded product reaches 800 mPa.s, stirring is stopped to obtain the second mixture; and / or In step 3), when the viscosity of the product obtained by the gel transformation reaches 1000 mPa.s, stirring is stopped and the mixture is cooled to obtain the third mixture.
9. The method according to any one of claims 6 to 8, It is characterized in that The temperatures of the first mixing and the second mixing are independently 160° C. to 163° C.; and / or In step 3), the gelation transition is performed at 170°C.
10. Use of the water-controlling sealing particles according to any one of claims 1 to 5 or the water-controlling sealing particles prepared by the method according to any one of claims 6 to 9 as water-controlling sealing agents for acid fracturing in water plugging of high-temperature, high-salinity fracture-cavity carbonate reservoirs; Preferably, the HCl content in the acid fracturing fluid is up to 5 wt%; and / or the high temperature is up to 140° C.; and / or the high salt has a mineralization degree of up to 210,000 mg / L.
Citation Information
Patent Citations
Oil-soluble temporary plugging agent and preparation method therefor
CN105062443A
Oil-soluble temperature-sensitive resin plugging agent for protecting reservoir as well as preparation method and application of oil-soluble temperature-sensitive resin plugging agent
CN113480984A
Ultrahigh-temperature-resistant particle plugging agent and preparation method thereof
CN114479800A
Carbonizing agent having improved affinity with resin and its manufacturing method
JP2005350602A
Plugging agent with temperature-resistant, salt-resistant and high-expansion for plugging large fractures and preparation method thereof
US10889745B1
